ANALISIS PENGARUH KUALITAS MARKETPLACE TOKOPEDIA TERHADAP KEPUASAN PENGGUNA MENGGUNAKAN METODE END USER COMPUTING SATISFACTION (EUCS) - Syahril; Diansyah, Risnal; Purnomo Pranoto, sudrajat (Department of Information System Muhammadiyah University of Riau, 2022)
Tokopedia is an online buying and selling website (e-commerce) in Indonesia that carries the Marketplace business model. In an effort to achieve efficiency in user satisfaction with the Tokopedia Marketplace, the EUCS method is used. Based on 5 independent variables in EUCS, namely Content (content), Accuracy (accuracy), Format (format), Ease of Use (ease of use) and Time linesss (timeliness). Data collection was carried out by distributing questionnaires to the Pekanbaru community using Tokopedia, from distributing the questionnaire 100 data were taken as samples to measure the satisfaction of Tokopedia marketplace users. Then it is known that the level of satisfaction with the content of information (Content) is 76.4%, Satisfaction with the accuracy of information (Acuracy) is 74.46%, Satisfaction with Display (Format) is 77.53%, Satisfaction with user convenience (Ease of Use) of 78.66%, and satisfaction with Timelines of 75.9%.